Evaluation of Median Road Development - Sunaryo; Natalia Reza Kusumawati (Jurnal Teknologi Transportasi dan Logistik, 2020)
Along with development, the need for road use is very important. Good for people who are in pedessaan and urban. Especially create the welfare of society that will be able to achieve these goals. Transportation in Indonesia is primarily ground transportation very often used by road users. Many problems arise such as congestion, accidents and other problems. The government has well planned road infrastructure and users are required to maintain existing facilities. Lane separator (median) which is a facility that affect the traffic characteristics. The placement and impact of road construction is taken into account. With the aim of separating the opposite traffic flow so that road effectiveness can be improved.